Volatilização de amônia e produtividade de milho no cerrado brasileiro após a aplicação de ureia formaldeído - Matos, Fabiano Bernardo (2019)
Among the elements required in corn, nitrogen (N) is the nutrient that provides the greatest effects on productivity components. However, the sources of ammoniacal N are subject to losses due to volatilization, mainly in the predominance of high temperatures, soil moisture at the moment of fertilizer application, soil type, N source used and nitrogen fertilizer management. The objective of this work was to evaluate the effects of urea and urea formaldehyde on corn and N losses by volatilization in two soil conditions (sandy soil and clayey soil). The experiment was carried out in the field, in the municipality of Sinop - MT. The experimental design adopted in the two soil conditions was in blocks with 7 treatments and 5 replicates, being: 2 treatments of urea formaldehyde incorporated together with corn sowing (50 and 80 kg ha-1 of N), 2 treatments of urea formaldehyde (50 and 80 kg ha-1 of N) 2 health treatments incorporated in coverage without stage v.4 of the culture (50 and 80 kg ha-1 of N) and the control. The morphological components of the corn plant, nitrogen, nitrogen extraction and export and NH3 volatilization were evaluated. The application of nitrogen via urea and urea formaldehyde increases maize productivity. The formaldehyde urea reduced as losses of N by volatilization. The application of nitrogen via urea and urea formaldehyde increases maize productivity.